Isokinetic performance of U-13 futsal athletes after application of the FIFA 11+ protocol (Fisioterapia e Pesquisa, 2019)
This study’s objective was to evaluate U-13 futsal players’ knee flexor and extensor muscles isokinetic performance, after a 18-week application of the FIFA 11+ protocol. Participants were male futsal players (n = 14) with a mean age of 12.58 ± 0.66 years. The force evaluation was performed pre- and post-intervention using the Biodex System Pro 4™ isokinetic dynamometer, at speeds of 60°/s, 180°/s, and 300°/s. The FIFA 11+ protocol was applied before the start of each regular training, twice a week, for 18 weeks, with an approximate duration of 25 minutes. In the pre-intervention analysis, a higher than 10% difference between dominant and non-dominant limbs was found in flexors’ and extensors’ peak torque, at the 60°/s and 180°/s speeds, respectively. In the postintervention analysis, no such asymmetries were found. Post-intervention, there was an increase in the agonistantagonist ratio on the dominant side, at the 60°/s speed, approaching the ideal value proposed in the literature (60%). There was also an increase in athletes’ isokinetic performance. The 18-week application of the FIFA 11+ protocol promoted an improvement in the isokinetic performance of the knee’s extensor and flexor muscles, and decreased the muscular asymmetries between the limbs of young futsal athletes.